ANALYSIS OF BRAKING MODES WITH APPLICATION OF HYDROSHOCK ABSORBERS FOR MECHANISMS OF INCREASED OPERATION SPEED - Maria S. KILINA; Vladimir A. TCHERNAVSKIY (Advanced Engineering Research)
Braking modes with application of hydroshock-absorbers for MECHANISMS OF INCREASED OPERATION SPEED are analyzed. Improvement tasks of hydroshock-absorbers for process equipment are formulated.